MORPHOLOGY, TAXONOMY AND DISTRIBUTION OF THE CRETACEOUS CORAL GENUS PREVERASTRAEA (LATE BARREMIAN-CENOMANIAN; SCLERACTINIA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2007)
The Cretaceous coral genus Preverastraea is being revised, mainly on the basis of sample material. This cerioid, occasionally astreoid or phaceloid, genus is characterised by round or polygonal calices, compact septa in a regular hexameral symmetry and lonsdaleoid septa. The wall is of the same structure as the septa. The genera Bogdanovicoenia, Paraacanthogyra, and Saxuligyra are considered synonyms of Preverastraea. Related genera are Aulastraeopora and Apoplacophyllia, which only differ by their solitary or dendroid growth forms. There are altogether 13 species of Preverastraea. The genus, which occurred worldwide, is restricted to the period from the Late Barremian to the Late Cenomanian, being most common in the Aptian to Early Albian. Eighty-three samples are either known from the literature or have been to hand. This makes Preverastraea a rather rare genus.
Keywords: Scleractinian corals; Preverastraea; Cretaceous; Systematics; Italy